Abnormal Auditory N100 Amplitude: A Heritable Endophenotype in First-Degree Relatives of Schizophrenia Probands - Turetsky, Bruce I. (2008)
BACKGROUND: N100 evoked potential amplitude and gating abnormalities have been widely observed in schizophrenia patients. However, previous studies have been inconclusive as to whether similar deficits are present in unaffected family members. The Consortium on the Genetics of Schizophrenia (COGS) is a multi-site NIMH initiative examining neurocognitive and neurophysiological measures as endophenotypes for genetic studies of schizophrenia. We report initial results, from the COGS dataset, of auditory N100 amplitude and gating as candidate endophenotypes. METHODS: Evoked potential data were acquired from 142 schizophrenia probands, 373 unaffected 1(st)-degree relatives and 221 community comparison subjects (CCS), using an auditory paired-click stimulation paradigm. Amplitude of the N100 response to each click and the click2/click1 ratio were dependent variables. Heritability was estimated based on kinships, using Solar v.2.1.2. Group differences were examined after subjects were categorized as either “broad” or “narrow”, based on the presence (“broad”) or absence (“narrow”) of non-psychotic psychiatric co-morbidity. RESULTS: Heritability estimates were .40 and .29 for click1 and click2 amplitudes and .22 for the ratio. “Broad” and “narrow” patients both had impaired click1 amplitudes. “Broad” relatives, but not “narrow” relatives, exhibited similar impairments. There were no group differences for either click2 amplitude or the gating ratio. CONCLUSIONS: N100 amplitude is a heritable measure that is abnormal in patients and a subset of relatives for whom psychiatric co-morbidity may be a genetically associated phenotype. Auditory N100 gating, although heritable, is less viable as a schizophrenia endophenotype.